(untitled) (Książnica Śląska, 2025)
The author presents the book collection of the Institut für Oberschlesische Landesforschung, transferred to the Biblioteka Śląska after World War II by the Zbiornica Księgozbiorów Zabezpieczonych in Katowice. It consists of over three hundred duplicated typescripts, published by the Publikationsstelle des Preußischen Geheimen Staatsarchivs. These are scientific publications in the field of social sciences, economics and geography translated into German.